Assesment Online Learning System di Masa Pandemi COVID-19 Menggunakan Metode Technology Acceptance Model - Yulius Hari; Darmanto; Budi Hermawan; Yonatan Widianto; Indra Budi Trisno (Universitas Negeri Gorontalo, 2020)
In the situation of a pandemic novel COVID-19 throughout the world forced all changes in the order of activities that exist in society, one of which is in teaching and learning activities. As a solution to learning activities at the moment everything must be implemented online, both students and instructors are forced to adapt to the online learning system . This sudden change often causes problems related to learner's behavior. This study tries to observe student behavior towards learning activities that are forced to be done from home with the principle approach of the Technology Acceptance Model (TAM). The research respondents numbered 93 people and the elearning system tested was the use of learning media with whatsapp, LMS Moodle, zoom meeting and its combination. The results of this study can provide recommendations in distance learning in the future.